Research trends on wheelchair basketball: A bibliometric review - Flórez-Gil, E.; Blanco-Martinez, N.; Gonzalez-Devesa, D. (European Journal of Human Movement, 2025)
Wheelchair basketball is played in more than 80 countries and is considered one of the Paralympic sports with the greatest audience and media impact. This study aimed a detailed analysis of the global scientific production around wheelchair basketball. A total of 314 journal publications between 1973 and 2024 were retrieved from the Scopus database using a specific search strategy. The findings point to a steady increase in the number of publications, particularly between 2020 and 2024, which constitutes more than 40% of the total output. Spain stands out as the country with the highest productivity, both in terms of publications and institutional output, with Turkey, Brazil, Japan and the United States following. In addition, the topics of the different articles with the highest impact focused on physical performance, injury prevention and classification. The scientific mapping showed a thematic progression from general demographic and methodological aspects in previous decades to more specific issues such as adapted sport, performance and disability in recent years. Joint word and keyword studies identified two main thematic clusters: one linked to research design and descriptors pertaining to the general population, and the other focused on concepts particular to sport and linked to disability. This bibliometric review highlights the academic progress of wheelchair basketball research and provides valuable insights to guide future studies, promote wider cooperation and inform evidence-based practices.